Co-firing: An exergoenvironmental analysis applied to power plants modified for burning coal and rice straw. (June 2016) - Restrepo, Álvaro; Bazzo, Edson
Abstract: An exergy approach to environmental impacts is proposed as an exergoenvironmental analysis methodology to be applied in a power plants modified for burning in a co-firing process, including external impacts originated from the routes of the coal and the biomass. A new Global Greenhouse Gases ( i G H G G l o b a l ) index is also presented in order to compare different co-firing scenarios. The methodology took into account the global warming impact category using the Global Warming Potential (GWP) index. The operating details were obtained from an existing 50 MWe PC power plant. Two scenarios were analyzed: (A) burning only pulverized coal; and (B) burning pulverized coal and rice straw in a co-firing process. The results showed a total of exergoenvironmental impact of 16.43 kg CO2-eq /s for scenario A and 12.3 kg CO2-eq /s for scenario B, that is, around 25.13% lower. In relation with the exergoenvironmental performance variables, the steam generator showed the highest environmental impact associated with the exergy destruction ( B ˙ D, k ) . Also, when scenario B was considered, the relative difference of specific environmental impact ( r b, k ) shows an important reduction around 30% lower in the steam generator. The ( i G H G G l o b a l ) index indicated values of 0.5 to scenario A and 0.564 to the scenario B. Graphical abstract: Highlights: A new exergoenvironmental approach is presented for PC power plants. Co-firing is proposed as alternative to mitigate the coal environmental impacts. The found results were validating in an existing 50 MWe PC power plant. The SimaPro and the GWP index were used as the tools for environmental analysis. A new Global Greenhouse Gases index is also presented.